2010
DOI: 10.1242/jeb.043588
|View full text |Cite
|
Sign up to set email alerts
|

On the role of copepod antennae in the production of hydrodynamic force during hopping

Abstract: SUMMARYWe integrate high-resolution experimental observations of a freely hopping copepod with three-dimensional numerical simulations to investigate the role of the copepod antennae in production of hydrodynamic force during hopping. The experimental observations revealed a distinctive asymmetrical deformation of the antennae during the power and return strokes, which lead us to the hypothesis that the antennae are active contributors to the production of propulsive force with kinematics selected in nature in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 47 publications
0
23
0
Order By: Relevance
“…The turbulent drag law applied by Huntley and Zhou [9], in contrary, is only valid for high Reynolds number flow (). Swimming of most zooplankton organisms, however, is associated with Reynolds numbers in the transitional range [53][55], where both approaches are not valid. Our measurements show that in the hydrodynamic trails of Daphnia , kinetic energy is dissipated at rates even exceeding current estimates.…”
Section: Discussionmentioning
confidence: 99%
“…The turbulent drag law applied by Huntley and Zhou [9], in contrary, is only valid for high Reynolds number flow (). Swimming of most zooplankton organisms, however, is associated with Reynolds numbers in the transitional range [53][55], where both approaches are not valid. Our measurements show that in the hydrodynamic trails of Daphnia , kinetic energy is dissipated at rates even exceeding current estimates.…”
Section: Discussionmentioning
confidence: 99%
“…It is therefore interesting to consider how other strategies for generating propulsion may also vary with size for other animals within this regime. For example, copepods (100<Re<1000) propagate a wake from their antennae to abdominal paddles during impulsive 'hopping' (Borazjani et al, 2010). This mechanism could fail as a result of viscous attenuation at lower Reynolds numbers, or could lack the necessary cohesion at larger scales.…”
Section: Swimming At Intermediate Reynolds Numbersmentioning
confidence: 99%
“…For example, Visser () utilized a far‐field multipole representation of prey‐induced Stokes flows to study the spatial variation of hydrodynamic flow signals at the first antenna. Others have addressed the effect of the copepod itself on flow fields near the body that could be sensed by setae, variously modeling the copepod as an infinite cylinder (Bundy et al ), a sphere (Jiang et al ; Jiang and Paffenhöfer ; Jiang and Strickler ), a plane wall or spheres depending on which part of the copepod is closest to the prey (Jiang and Paffenhöfer ), or even considering the detailed geometry of a copepod (Jiang et al , ; Gilmanov and Sotiropoulos ; Borazjani et al ). Generally, it is found that flows near the body, including at setae, are significantly affected by hydrodynamic interactions with the copepod itself.…”
mentioning
confidence: 99%